Management and outcomes of 27 pregnancies in women with myeloproliferative neoplasms. (2nd January 2020) - Lapoirie, Joëlle; Contis, Anne; Guy, Alexandre; Lifermann, François; Viallard, Jean-François; Sentilhes, Loïc; James, Chloé; Duffau, Pierre
Abstract: Introduction: Philadelphia-negative myeloproliferative neoplasms (MPNs) greatly increase the risk of maternal and fetal complications during pregnancy. Currently, international agreements regarding the management of these women are lacking. Patients and methods: Our study aimed to assess the current management and outcomes of MPN pregnancies in a French cohort. We retrospectively analyzed 27 pregnancies in women with MPNs that were associated with a specific mutation. Nineteen pregnancies in nine women with essential thrombocythemia and eight pregnancies in five women with polycythemia vera were identified. Results: Our study showed 70% live births, but only 30% uneventful pregnancies. Fetal complications were mainly early spontaneous abortions (22%), fetal growth restriction (15%), and premature delivery (15%). Maternal issues were divided between thrombosis (15%) and hemorrhages (11%). High rates of preeclampsia and hemolysis, elevated liver enzymes, and low platelet count syndrome (15%) were reported. Uterine artery Doppler was performed in 70% pregnancies. Abnormal Doppler results were found in 43% pregnancies. Pregnancies with high platelet counts and packed cell volume remaining static or increasing ended with fetal death and utero-placental dysfunction. According to expert consensus, most of the pregnancies (67%) could be stratified in the high risk group and had a bad obstetrical outcome, with 50% standard-risk pregnancies versus 22% high-risk pregnancies that were uneventful. Higher risk pregnancies were prescribed heparin and/or interferon α in 72%. Conclusions: The prognosis of these pregnancies remains very bad and may be improved by a more effective collaboration between specialists as well as a therapeutic intensification including heparin and interferon α.